THE ROLE OF INFORMATION COMMUNICATION TECHNOLOGY ON ORGANIZATIONAL ABILITY, MARKET ENVIRONMENT AND FINANCIAL PERFORMANCE - Sri Maryati; Muhammad Ichsan Siregar; Abdullah Saggaf (AKUNTABILITAS, 2022)
The purpose of this study to test the role of the Information Communication of Technology (ICT) innovation on the relationship between organizational capabilities, and the market environment against company performance. There are still a few studies that connect between the ability of the organization and the market environment through the role of ICT to improve the company's performance into motivation in this study. This research was conducted on MSMEs in Palembang City. This research is quantitative, using primary data obtained through the deployment of the questionnaire, using the purposive sampling method. Then the data was analyzed using Smart-Pls help to test the effect of mediation. The results of the analysis show the ability of the organization influence the adoption of ICT, and the market environment has also influenced the adoption of ICT. In addition, the role of ICT is able to become a liaison between organizational capabilities, and market environment on company performance.